Business, BTEC National level 3. Book 2 - Bevan, John.; Edexcel (Organization) (Harlow : Pearson Education, 2010)
This student book includes all four mandatory units plus eight popular optional units providing complete coverage for the BTEC Level 3 National Supplementary Award. Assignment activities give practice for all grading criteria for the units covered, with Edexcel's own assessment tips written by BTEC Level 3 National experts.
At head of title: Edexcel.
Includes bibliographical references and index.
Keywords: Business; Business and Management